SARS-CoV-2 mutations: phenotypes and implications for vaccine development - Montefiori, David (Henry Stewart Talks, 2021)
Currently known SARS-CoV-2 strains, Likelihood of mutating into a more lethal form of SARS-CoV-2, Spike proteins and their role in viral entry into human cells, SARS-CoV-2 is mutating into a more transmissible or infectious form, Implications of new SARS-CoV-2 variants on public health and vaccine development, Importance of continuing genetic surveillance of the virus.